TANGENTIAL MOVEMENTS OF DNIPER-DONETS DEPRESSION AS ONE OF THE FACTORS OF FORMATION OF OIL- AND GAS-BEARING STRUCTURES - Lazaruk, Ya. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The modern structure of the Dnieper-Donets Depression (DDD) has been formed as a result of vertical dipherential movements of the basement blocks and under the influence of salt tectonics. We propose new factor of the formation of the region structure. This approach substantiated the horizontal tangential movements of the earth crust. We reconstructed a scheme of possible tangential stresses. This scheme together with vertical movements of the basement and salt tectonics have led to the formation of the modern structural layout of DDD. Tangential movements caused by regional right-handed displacement have been manifestated on the background of transverse strain during Paleozoic in DDD. A system of echelon folding of the first generation located at angle of about 30º to the axis of depression has been formed in the field of tangential stresses in graben. Conjugated systems of the structure splitting have been formed in the field of stress in the main displacement according to the direction of the effect of maximum tangential stresses,. Synthetic ones were orientated at angle of 10-15º to the axis of the depression and antisynthetic ones located at angle of 75-80º to the axis of the region. These are systems of structures of the second generation manifestateded in the form of rightechelon and left-echelon groups of folds. Within the northern edge of DDD a number of structures also is oriented at angle to the region`s strike and coincides with the direction of the main maximum stresses.